2001
DOI: 10.1021/la001781k
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of Fatty Acid Monolayer Phases Due to Ionization of the Headgroups

Abstract: Monolayers of simple fatty acids exhibit a rich polymorphism with at least seven solid phases. The reason for such a variety of phases is not known yet and therefore is the object of the current investigation. In the present work the pH of the subphase is varied between 2 and 10.5 and the influence of the degree of dissociation on phase transition pressures and temperatures of arachidic acid monolayers is investigated in detail in the range from 2 to 45 °C by means of Brewster-angle microscopy and surface pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 66 publications
7
57
0
Order By: Relevance
“…This is manifested in the shift of the phase coexistence lines to lower temperatures. These results are in qualitative agreement with experiments carried out in fatty acid monolayers with ionic head groups [45].…”
Section: Phase Diagramssupporting
confidence: 91%
See 2 more Smart Citations
“…This is manifested in the shift of the phase coexistence lines to lower temperatures. These results are in qualitative agreement with experiments carried out in fatty acid monolayers with ionic head groups [45].…”
Section: Phase Diagramssupporting
confidence: 91%
“…It has been found experimentally that the long-range repulsive interactions between molecular heads lead to the monolayer's rich structure and phase behavior. It is known that head-head interactions are modulated by partial dissociation when the subphase pH is varied [43][44][45]. For instance, in aqueous solutions of soaps with a pH between 7.0 and 10.0, the heads of long-chain fatty acids are partially ionized [12,43], while strong changes in the head-head interactions are expected when metal ions are present in the subphase [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies at the air/water interface have indicated the phase behavior of fatty-acid monolayers remains unchanged for pH values less than 9.0. [47][48][49] The pK a values for fatty acids in a monolayer state were measured to be markedly greater than that of a solution state though the reason for this remains unclear. 47 Attempts to carry out our studies at a lowered pH of 4.0 caused our monolayer to collapse as the temperature was lowered.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid monolayer phase transitions can also be studied using methods such as X-ray diffraction (31)(32)(33)(34)(35)(36), FT-Raman spectroscopy (35), and Brewster angle microscopy (BAM) (36,37). A correlation between fatty acid monolayer phase transition and solution pH has been shown using the BAM technique (37). Specifically, spread monolayers of fatty acids show maximum resistance to phase transition under compression when the pH of the solution equals the pK a , indicating that the L 2 phase, which is characteristic of fatty acid monolayers, is stabilized by the ion-dipole interactions between carboxylic acid and carboxylate headgroups (Fig.…”
Section: Figmentioning
confidence: 99%